Human Cytomegalovirus Long Non-coding RNA1.2 Suppresses Extracellular Release of the Pro-inflammatory Cytokine IL-6 by Blocking NF-κB Activation - Lau, Betty; Kerr, Karen; Gu, Quan; Nightingale, Katie; Antrobus, Robin; Suárez, Nicolás M.; Stanton, Richard J.; Wang, Eddie C. Y.; Weekes, Michael P.; Davison, Andrew J. (Frontiers in Cellular and Infection Microbiology, 2020)
Long non-coding RNAs (lncRNAs) are transcripts of >200 nucleotides that are not translated into functional proteins. Cellular lncRNAs have been shown to act as regulators by interacting with target nucleic acids or proteins and modulating their activities. We investigated the role of RNA1.2, which is one of four major lncRNAs expressed by human cytomegalovirus (HCMV), by comparing the properties of parental virus in vitro with those of deletion mutants lacking either most of the RNA1.2 gene or only the TATA element of the promoter. In comparison with parental virus, these mutants exhibited no growth defects and minimal differences in viral gene expression in human fibroblasts. In contrast, 76 cellular genes were consistently up- or down-regulated by the mutants at both the RNA and protein levels at 72 hours after infection. Differential expression of the gene most highly upregulated by the mutants (Tumor protein p63-regulated gene 1-like protein; TPRG1L) was confirmed at both levels by RT-PCR and immunoblotting. Consistent with the known ability of TPRG1L to upregulate IL-6 expression via NF-kappaB stimulation, RNA1.2 mutant-infected fibroblasts were observed to upregulate IL-6 in addition to TPRG1L. Comparable surface expression of TNF receptors and responsiveness to TNF-α in cells infected by the parental and mutant viruses indicated that activation of signalling by TNF-α is not involved in upregulation of IL-6 by the mutants. In contrast, inhibition of NF-kappaB activity and knockdown of TPRG1L expression reduced the extracellular release of IL-6 by RNA1.2 mutant-infected cells, thus demonstrating that upregulation of TPRG1L activates NF-kappaB. The levels of MCP-1 and CXCL1 transcripts were also increased in RNA1.2 mutant-infected cells, further demonstrating the presence of active NF-kappaB signalling. These results suggest that RNA1.2 plays a role in manipulating intrinsic NF-kappaB-dependent cytokine and chemokine release during HCMV infection, thereby impacting downstream immune responses.